Pharmacovigilance in Israel - tools, processes, and actions - Eyal Schwartzberg; Matitiahu Berkovitch; Dorit Dil Nahlieli; Joseph Nathan; Einat Gorelik (BMC, 2017)
Abstract Background Due to the limited safety data available at the time that a new medication is first marketed, it is essential to continue the collection and monitoring of safety data about adverse drug reactions (ADRs) during the medication's life cycle. This activity, known as pharmacovigilance (PV), is performed worldwide by the pharmaceutical industry as well as by regulatory agencies. In 2012, the Israeli Ministry of Health (MOH) established a Pharmacovigilance and Drug Information Department. The Department is tasked with identifying, monitoring, and initiating activities aimed at minimizing risks associated with medication utilization. To enable this, the MOH has devised procedures for PV and promoted extensive legislation in this area that require marketing authorization holders (MAHs) and medical institutions in Israel to report ADRs and new safety information to the MOH. A computerized database was created to support the reporting process. The objective of this article is to characterize the PV tools and activities implemented in Israel. Methods Since September 2014, The Israeli Pharmacovigilance and Drug Information Department receives ICSRs at a central computerized database developed for this purpose. The data were analyzed by Department personnel and ICSRs were characterized according to their seriousness, source, categories of drugs involved, and the reporting format. Additionally, the Department reviewed signals detected from ADR reports and from other sources and assessed the resulting regulatory actions. Results An analysis of the Individual Case Safety Reports (ICSRs) submitted to the MOH's ADRs central database reveals that during the review period, a total of 16,409 ICSRs were received by the Department and 850 signals were identified, resulting in the following PV activities: inquiry and enhanced follow-up (430, 50.6%), prescriber's and patient's leaflets updates (204, 24%), recall of products/batches (6, 0.7%), alerts for health care professionals (63, 7.4%). Eighty five (10%) of the signals required a comprehensive investigation involving external specialist and 1 (0.1%) resulted in initiation of epidemiologic study. Additionally, in 2015 the Department incorporated comprehensive framework for risk minimization of marketed medicinal products, also known as risk management plans (RMPs). Conclusions As practiced by other health authorities, the Israeli MOH effectively implemented various PV tools to ensure the safety of the Israeli health consumer.